2012
DOI: 10.4037/ccn2012662
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal Hypertension and Abdominal Compartment Syndrome

Abstract: Intra-abdominal hypertension has a prevalence of at least 50% in the critically ill population and has been identified as an independent risk factor for death. Yet, many of the members of the critical care team do not assess for intra-abdominal hypertension and are unaware of the consequences of untreated intra-abdominal hypertension. These consequences can be abdominal compartment syndrome, multisystem organ failure, and death. This article provides an overview of the pathophysiology of intra-abdominal hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 26 publications
0
60
0
4
Order By: Relevance
“…These consequences can be an abdominal compartment syndrome, multi-system organ failure, and it may lead to mortality rate of 40%-100%. [1,6] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These consequences can be an abdominal compartment syndrome, multi-system organ failure, and it may lead to mortality rate of 40%-100%. [1,6] …”
Section: Introductionmentioning
confidence: 99%
“…The pressure in the abdominal cavity is called intraabdominal pressure (IAP) and it is normally ranged from 0-5 mmHg in healthy person [1] and 5-7 mmHg in the general patient population. [2] Body weight, posture, abdominal muscles tension, and diaphragm movements all these factors are considerably affect IAP [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…In a multicenter epidemiological study performed in 6 countries analyzing the IAH prevalence in the intensive care unit, Malbrain et al (2004) reported that 57 critically ill patients (58.8%) were diagnosed with IAH and 8 (8.2%) with ACS. In a previous study, an IAP increase of up to 20 mmHg decreased the mesenteric perfusion by 40%, and an increase to 40 mmHg decreased the mesenteric perfusion by 70%; intestinal permeability portal vein endotoxin concentration both remarkably increased in response (Lee, 2012). A persistent IAP ≥ 15 mmHg is a reported independent risk factor for renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The steady-state abdominal cavity pressure, known as intra-abdominal pressure (IAP), ranges 0-5 mmHg and inversely varies with the intrathoracic pressure during normal respiration (Lee, 2012). Temporary IAP changes can be induced by numerous factors, including coughing, sneezing, and even loud singing.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The percentage of IAH in acutely ill patients is documented to be 50%, [10] of these, 50%, 32.1% develop IAH within their first 24h of ICU admission. [11,12] The concept of IAP and its impact on disorders in organ function in patients has significant interest grew. IAH not only affects the abdominal organs-but it affects various organ of the body like the respiratory system, blood dynamics and cerebral perfusion.…”
Section: Introductionmentioning
confidence: 99%